Alterations of insulin-like growth factor-1 receptor gene copy number and protein expression are common in non-small cell lung cancer. Issue 11 (12th August 2014) - Tran, T N; Selinger, C I; Yu, B; Ng, C C; Kohonen-Corish, M R J; McCaughan, B; Kennedy, C; O'Toole, S A; Cooper, W A
Abstract : Aims: Insulin-like growth factor-1 receptor (IGF1R) is a tyrosine kinase membrane receptor involved in tumourigenesis that may be a potential therapeutic target. We aimed to investigate the incidence and prognostic significance of alterations in IGF1R copy number, and IGF1R protein expression in resected primary non-small cell lung cancer (NSCLC), and lymph node metastases. Methods: IGF1R gene copy number status was evaluated by chromogenic silver in situ hybridisation and IGF1R protein expression was evaluated by immunohistochemistry in tissue microarray sections from a retrospective cohort of 309 surgically resected NSCLCs and results were compared with clinicopathological features, including EGFR and KRAS mutational status and patient survival. Results: IGF1R gene copy number status was positive (high polysomy or amplification) in 29.2% of NSCLC, and 12.1% exhibited IGF1R gene amplification. High IGF1R expression was found in 28.3%. There was a modest correlation between IGF1R gene copy number and protein expression (r=0.2, p<0.05). Alterations of IGF1R gene copy number and protein expression in primary tumours were significantly associated with alterations in lymph node metastases (p<0.01). High IGF1R gene copy number and protein expression was significantly higher in squamous cell carcinomas (SCC) compared with other subtypes of NSCLC (p<0.05). There were no other associations between IGF1R status and other clinicopathological features including patient age, gender, smoking status, tumour size, stage, grade, EGFR or KRAS mutational status or overall survival. Conclusions: High IGF1R gene copy number and protein overexpression are frequent in NSCLC, particularly in SCCs, but they are not prognostically relevant.